‘Social policy by other means?’ land reform, gender and welfare in Zimbabwe - Newman Tekwa; Jimi O. Adesina (Cogent Social Sciences)
The ‘social policy by other means’ literature, from the viewpoint of mainstream comparative welfare state research, frames land and agrarian reform as a ‘functional equivalent’ of and an ‘unconventional’ form of social policy. Framed within the transformative social policy perspective and focusing on gender, land, and agrarian reform in Zimbabwe, this paper problematizes such a conceptualisationfor reinforcing ethnocentrism with policy instruments not deployed in core OECD contexts seen as ‘lesser than’ social policy instruments. Two cross-sectional quantitative and qualitative studies gathered data using a combination of survey questionnaires, in-depth and key informant interviews and focus group discussions, with the first conducted in 2016 and subsequently in 2022. A comparative gender analysis of land reform vis-à-vis non-land reform beneficiary households, in addition to a before-and-after analysis of female relative to male-headed land reform beneficiary households, qualifies land and agrarian reform as another social policy instrument available to policymakers to be tasked with the intention of enhancement of welfare and well-being. Land reform must be included in the literature on social policies in the South. Theoretically, the paper contributes to ongoing welfare state debates about positioning social policy between growth and development.